Perencanaan Lanskap Pantai Pangandaran Berbasis Mitigasi Bencana Tsunami - RAMDHANY, RIZKY RAHADIAN; MAKALEW, AFRA DN (Jurnal Arsitektur Lansekap; Vol.2, No.1, April 2016, 2016)
ABSTRACT Coastal Landscape Planning in Pangandaran Based on Tsunami Disaster Mitigation The Indonesian archipelago has a long coastline of about 81,000 km. Some coastal areas in Indonesia, classified in areas with high risk of tsunami. The objective of this research was to develop a coastal planning in Pangandaran and provide recommendations related to tsunami disaster mitigation. The tsunami ever occurred at the site studied, namely in 2006. The method used in this study is a modification of the method of planning (Gold 1980) which comprise the step of preparation, inventory, analysis, synthesis, and planning. Analysis is conducted analysis of regional vulnerability to tsunamis. The results from the analysis found that Pangandaran beach is classified as an area highly vulnerable to tsunami, based on an assessment of the slope, elevation, land use, distance from the river and distance from the coast. Analysis of the suitability of the area for evacuation was conducted to determine the exact area used as a tsunami evacuation. The concept of planning is divided into space concept, the concept of activity, the concept of infrastructure, circulation concept and the concept of vegetation. The concept that there is then developed to produce a landscape plan, plan activities, circulation plan, vegetation plans, and plan infrastructure facilities. Keywords: coastline, mitigation, Pangandaran, planning, tsunami